Thyroid storm presenting as septic shock in the intensive care unit: A Case Series - Niraj Kumar Keyal; Niru Pokharel; Sudesh Khanal (Journal of Nepal Medical Association, 2020)
Thyroid storm is a rare endocrine emergency that rarely presents with septic shock. It occurs in thyrotoxic patients and is manifested by decompensation of multiple organs, triggered by severe stress. The diagnosis and response to treatment is made by Burch-Wartofsky point scale or Japanese thyroid association criteria due to lack of pathophysiology of thyroid storm. We reported series of patients that presented with altered sensorium, cough, fever, palpitation, shortness of breath and shock. Patient were treated initially for septic shock, later diagnosed as thyroid storm and was treated with oral carbimazole, propanolol and digoxin. From this, we want to emphasize that thyroid storm can have any presentation that should be kept in differential diagnosis of septic shock not responding to usual treatment; early diagnosis and treatment with oral medication can decrease morbidity and mortality in rural setting where intravenous form of antithyroid drug are not available for thyroid storm.